"The Media Covers Up a Lot of Things": Watchdog Ideals Meet Folk Theories of Journalism. (25th October 2020) - Palmer, Ruth; Toff, Benjamin; Nielsen, Rasmus Kleis
ABSTRACT: The idealized view of the press as an institution that operates independently from private and political interests and tries to hold power to account is central to many journalists' self-conception and extensive academic scholarship on news. Yet surveys find significant numbers of citizens reject such views about the role of news in society. This article draws on in-depth interviews with a strategic sample of 83 news avoiders in Spain and the UK to investigate "folk theories" about the relationship between news and politics. Instead of believing in the watchdog ideal, many saw the news media as, at best, irrelevant and, at worst, actively complicit with a distant and self-serving political and economic establishment. Many saw the news not as bringing important subjects to light, but as actively covering them up. The difference between professional and scholarly theories that stress the watchdog role on the one hand, and folk theories where this notion is completely absent on the other, highlights the specific cultural challenge journalism faces today. Cynicism about the role of news in society poses a problem that transcends the specific economic, political, and technological challenges that currently preoccupy many journalism professionals and institutions.